Pendampingan dan Pengembangan UMKM Kupang Lontong Balap Pak Warno Pasca Pandemi Covid-19 - Gita Widi Bhawika; Mochammad Andy Rizqy; Bertonius Vrando Haloho; Arsyta Dewi Tri Cahyani; Alvionita Vernica Shaf Akhdina; Sonia Zaki Aditya; Nunik Isyidhun Nai’mah; Muhammad Baskoro Aji (Jurnal Pemberdayaan Umat, 2023)
Purpose: This community service activity aims to: (1) Identify the current conditions of the marketing and sales activities of the UMKM Kupang Lontong Balap Pak Warno to expedite traditional culinary development efforts in the post-covid-19 pandemic era through social entrepreneurship; (2) Developing Lontong Kupang innovation products in the form of Frozen Food with UMKM Kupang Lontong Balap Pak Warno; And (3) Designing appropriate business processes including digital marketing and online sales for UMKM Kupang Lontong Balap Pak Warno, which can then be duplicated and adapted for other regions in Indonesia. Method: This was done by developing the Kupang Lontong Balap Pak Warno MSME business through Lopang product innovation in the Post-Covid-19 Pandemic Era using the Design Thinking approach, Social Business Model Canvas, and Value Proposition Design. Result: The results of observations made in community service to develop the Kupang Lontong Balap Pak Warno MSME business, the author succeeded in formulating a Value Proposition Design for this MSME after conducting group discussion forums and online surveys Conclusion: This service activity was carried out were the creation of instant kupang rice cake product innovations, digitalization of sales using the online shop platform, and transformation of financial records using the SiApik accounting application.